A field study of the impact of psychotropic medication on delinquency and juvenile justice system involvement among a high risk sample of children and adolescents. Issue 6 (17th August 2020) - Armstrong-Hoskowitz, Natalie; Schmidt, Adam T.; Henderson, Craig E.; Nelson, David V.; Allen, Brian J.
Abstract: At-risk youth are more likely to engage in delinquent behaviors and be involved in the juvenile justice system (JJS). Improving outcomes for such youth increasingly include long-term administration of psychotropic medications (PM). Current research addresses short-term utility of PM, but evidence is mixed regarding long-term effectiveness. Using a large, cross-national, at-risk youth sample (n = 2065), this study examined how PM influenced total delinquent behaviors in a given year, and JJS entry, over a seven-year time period. PM treatment did not significantly decrease delinquent behaviors among youth; nor prevent entry into the JJS. Implications for policy and practice are discussed.